Second reported case of multilocularis hydatid disease in Iraq - Zeki Benyan, A.K.; K. Mahdi, N.; Abdul-Amir, F.; Ubaid, O. (Scientific Journal of Medical Science, 2014)
Hydatid disease is an important zoonotic disease with a world wide distribution. In Middle East as well as in some other parts of the world, it has always been a serious economic and public health problem. The disease is endemic and enzootic in Iraq. In Iraq, the disease is caused by Echinococcus granulosus but a multilocular hydatid cyst of E.multilocularis has been recovered from the liver of a woman in Erbil (North Iraq).